Design of a polarization independent terahertz metamaterial absorber for biomedical sensing applications - Tasnim Mahfuz; Arif Hossan; Naymur Rahman (Biosensors and Bioelectronics: X)
Metamaterial absorbers (MMAs) are currently highly desirable because of their special absorption qualities. In this paper, a highly simplified and optimized terahertz MMA is proposed and analyzed for sensing applications. The proposed MMA is polarization-independent because of its symmetrical structure. Its symmetrical structure is achieved through the utilization of L-shaped gold patches. Being polarization-independent means that terahertz waves of any polarization can be efficiently absorbed by it. The proposed design consists of several L-shaped gold metallic patches over a polyimide substrate and a ground plane. It achieves an absorption of 96% at a specific frequency of 1.672 THz with a quality factor of 28.26. The quality factor indicates a sharp resonance peak, which is crucial for accurate sensing measurements. The absorber's resonance frequency changes with its surrounding medium's refractive index (RI). Thus, the MMA can also be used as a RI sensor. The RI has varied in the range of 1.304–1.342. The average sensitivity of the proposed sensor is 374 GHz/RIU. It is important to note that most biomedical samples have RI ranges from 1.3 to 1.39, making the proposed sensor highly suitable for a broad range of biomedical applications. The biomedical applications include non-invasive detection of subtle changes within tissues, monitoring drug delivery processes or even early-stage disease diagnosis.